Computational modelling to determine the physical characteristics of biological tissues for medical diagnosis. (10th November 2020) - Polyakov, Maxim
Timely diagnosis of breast cancer is an important task. The method of microwave radiothermometry is a promising direction for solving this problem. Computer simulations are used to improve the quality of diagnostics. It is necessary to build personalised models, taking into account the individual nature of the internal structure of the mammary gland in each patient. One of the problems is the determination of biophysical characteristics of biological components. Methods for determining these characteristics using computer simulations are proposed. The coefficient of thermal conductivity and specific heat of biological tissues are determined from known temperature distributions. The results obtained are in good agreement with previously known exact solutions, which indicates the applicability of this method for solving this class of problems. The efficiency of using parallel technologies in solving the inverse problem is investigated and the applicability of open MP technology is demonstrated.